Overexpression and crystallization of 205Y lipase from Bacillus sphaericus 205Y - Hamooni, Sayyedeh Hoda (2017)
Lipases are ubiquitous in nature and produced by different plants, animals and microorganisms. They catalyse hydrolysis as well as the reverse reaction, esterification, transesterification and interesterification. Structural studies and X-ray crystallography of lipases can provide clues towards understanding their properties and function. Previously, the gene encoding 205y lipase was isolated from Bacillus sphaericus 205y, cloned into the pUC19 vector and expressed extracellularly in Escherichia coli TOP10 host. The gene encoding mature lipase (without signal peptide and transmembrane) was cloned into the pBAD vector and expressed intracellularly in E. coli TOP10 host. This enzyme was purified and characterized as an organic solvent tolerant lipase. However, the recombinant cells harbouring pUC19/205y and pBAD/205y-SP-TM showed low expression of target protein that was not sufficient for crystallization. Therefore, high levels of protein expression and obtaining the best quality crystal suitable for X-ray diffraction were the desired goals of this research. Comparative sequence analysis of 205y lipase gene along with phylogenetic tree explored a new family in lipases classification, family IX. The 205y lipase gene was resynthesized to remove 16 rare codons in the gene sequence. The resynthesized gene was cloned into pET-16b vector and transferred into E. coli Top10. In order to overexpress the 205y lipase gene, different parameters were optimized. The recombinant pET-16b/205y vector was subtransformed into three different expression hosts and the highest expression was achieved by E. coli Roseta-gami pLysS (DE3). The highest 205y lipase activity was 118 U/mL using p-NP decanoate as substrate. The 205y enzyme was purified using two steps of hydrophobic interaction chromatography (HIC) and gel filtration (GF) chromatography to 55% recovery with 3.3 fold purification. To screen for crystallization, different formulations from three screening kits were used. Formulation of crystal screen I No 16 composed of 150 mM sodium citrate tribasic dihydrate, (pH 5.6), 20% 2-propanol, 20% polyethylene showed the best result. Subsequently, to obtain a high quality crystal, the formulation was optimized using different parameters such as protein concentration, buffer, precipitant and temperature in setting drop vapour diffusion technique. Izit Crystal Dye (Hampton Research, USA) was used to distinguish the protein crystal from salt crystal. The attempt to diffract the 205y lipase crystal using in-house X-ray diffractometer system (Bruker AXS) was able to be processed. The diffraction images were collected and they showed good intensity and regular reflection spots at 2.25Å resolution. In conclusion, the 205y lipase gene with a few closed isolated genes from GenBank databased was represented as a new family of lipases (family IX). The expression of lipase under the control of chemically inducible T7 promoter was higher than other previously tested promoters. In addition, the high level expression led to appropriate amount of pure protein for crystal optimization. Ultimately, the proper size and quality crystal was formed and successfully X-ray diffracted.